ANTENNA’S SYSTEM PROCESSOR DESIGN WITH DIGITAL BEAMFORMING USING FPGA - Ramírez Zaldívar, Alexander Rogelio; Hernández Violat, Abel; Ibarra Guerra, Yunior (Telemática, 2020)
Digital beamforming constitutes one of the actual tendencies in the construction of the antenna’s array. The paper presents the core’s realization for an electronic beam scan system in FPGA from the digital design made in Simulink (MATLAB), and exported to VHDL for its synthesis in the programmable logic device. The work gets a method to develop and fine-tunes this kind of processor that can be extended to more complex applications within this job’s line like smart antennas with adaptive data processing. The main contribution is the processor’s implementation for a digital array with an electronic scan from the description made in MATLAB.